The Role of Interleukin-1 Beta C-511T as a Modifier Polymorphism in Cryopyrin-associated Periodic Syndromes - Berk Özyılmaz; Taha Reşid Özdemir (Journal of Pediatric Research, 2019)

(untitled)
Aim:Cryopyrin-associated Periodic Syndromes (CAPS) are a subgroup of the Periodic fever syndromes, caused by mutations in the NLRP3 gene. NLRP3 gene mutations can cause three clinically different phenotypes. It is known that even the same mutations in the NLRP3 gene can cause different phenotypes. To investigate this situation, we have constructed a hypothesis that if an individual with the Interleukin-1 Beta (IL-1β)-511 T/T genotype which is associated with overexpressed IL-1β levels, he/she might have a more severe CAPS phenotype.Materials and Methods:Thirty-six NLRP3 Exon three variant-positive patients with detailed clinical data and 30 healthy controls were selected for the IL-1β genotype investigation. For the analysis of IL-1β-511 allele, the SNP rs1143634 was genotyped using the TaqMan 5’-exonuclease allelic discrimination assay.Results:Neither the Muckle Wells Syndrome patients (severe phenotype) with a p.Val198Met mutation nor symptomatic patients with the p.Gln703Lys variant showed an increased IL-1β-511T/T genotype frequency.Conclusion:We suggest that IL-1β-511 T/T polymorphism is not a modifying factor regarding the clinical severity of CAPS patients. However, to expand this theory and in order to find other modifying genetic factors, other polymorphisms of IL-1β or other genes in the inflammasome pathway such as caspase-1 or ASC should be analyzed.